SPAdes: a new genome assembly algorithm and its applications to single-cell sequencing - Bankevich, Anton; Nurk, Sergey; Antipov, Dmitry; Gurevich, Alexey A; Dvorkin, Mikhail; Kulikov, Alexander S; Lesin, Valery M; Nikolenko, Sergey I; Pham, Son; Prjibelski, Andrey D; Pyshkin, Alexey V; Sirotkin, Alexander V; et al. (Journal of computational biology, 2012)
The lion's share of bacteria in various environments cannot be cloned in the laboratory and thus cannot be sequenced using existing technologies. A major goal of single-cell genomics is to complement gene-centric metagenomic data with whole-genome assemblies of uncultivated organisms. Assembly of single-cell data is challenging because of highly non-uniform read coverage as well as elevated levels of sequencing errors and chimeric reads. We describe SPAdes, a new assembler for both single-cell and standard (multicell) assembly, and demonstrate that it improves on the recently released E+V-SC assembler (specialized for single-cell data) and on popular assemblers Velvet and SoapDeNovo (for multicell data). SPAdes generates single-cell assemblies, providing information about genomes of uncultivatable bacteria that vastly exceeds what may be obtained via traditional metagenomics studies. SPAdes is available online ( http://bioinf.spbau.ru/spades ). It is distributed as open source software.